2001
DOI: 10.1074/jbc.m008851200
|View full text |Cite
|
Sign up to set email alerts
|

Modular Motif, Structural Folds and Affinity Profiles of the PEVK Segment of Human Fetal Skeletal Muscle Titin

Abstract: The extension of the PEVK segment of the giant elastic protein titin is a key event in the elastic response of striated muscle to passive stretch. PEVK behaves mechanically as an entropic spring and is thought to be a random coil. cDNA sequencing of human fetal skeletal PEVK reveals a modular motif with tandem repeats of modules averaging 28 residues and with superrepeats of seven modules. Conformational studies of bacterially expressed 53-kDa fragment (TP1) by circular dichroism suggest that this soluble prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
109
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 31 publications
7
109
0
Order By: Relevance
“…Other work focusing on the conformation of PEVK peptides has suggested that this region may contain some secondary structure [14][15][16][17][18]. Two types of repeat domains have been identified in the PEVK region [17].…”
Section: Introductionmentioning
confidence: 99%
“…Other work focusing on the conformation of PEVK peptides has suggested that this region may contain some secondary structure [14][15][16][17][18]. Two types of repeat domains have been identified in the PEVK region [17].…”
Section: Introductionmentioning
confidence: 99%
“…The segment appears to be involved in interfilament adhesion between thin filaments in both skeletal and cardiac muscles. In skeletal muscle, PEVK binds actin and nebulin, with only the PEVK/nebulin interaction being inhibited by Ca 2ϩ /S100A (25,29). This S100 sensitivity of the adhesion between PEVK and thin filaments was later observed in the cardiac muscle, resulting instead from its effect on PEVK/actin interaction (30).…”
mentioning
confidence: 96%
“…Pro is thus the second residue of the VPE consensus sequence. We have previously designated PE as the start of each module based on fetal PEVK exons (25). Other investigators have phased the PEVK module in the middle of the exons (54).…”
Section: Sh3-binding Motifs In Pevk Exons Of Titin and Titin-likementioning
confidence: 99%
See 2 more Smart Citations